2008
DOI: 10.1152/ajpcell.00218.2008
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of EP3 subtype in prostaglandin E2-induced adhesion of mouse cultured and peritoneal mast cells to the Arg-Gly-Asp-enriched matrix

Abstract: Accumulating evidence has indicated that mast cells can modulate a wide variety of immune responses. Migration and adhesion play a critical role in regulation of tissue mast cell function, in particular, under inflammatory conditions. We previously demonstrated that prostaglandin (PG) E(2) stimulates adhesion of a mouse mastocytoma cell line, P-815, to the Arg-Gly-Asp (RGD)-enriched matrix through cooperation between two PGE(2) receptor subtypes: EP3 and EP4 (Hatae N, Kita A, Tanaka S, Sugimoto Y, Ichikawa A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…These results indicate that PGE 2 -EP3-mediated vascular hyperpermeability depends on MCs. Indeed, we found that the EP3 receptor is abundantly expressed in BMMCs, as reported previously (38 ). After 5 wk, reconstitution and maturation of the transferred MCs in ear tissues were confirmed by monitoring gene expression of MC-specific genes (Supplemental Fig.…”
Section: Pge 2 -Induced Vascular Hyperpermeability Depends On Ep3 Recsupporting
confidence: 91%
See 1 more Smart Citation
“…These results indicate that PGE 2 -EP3-mediated vascular hyperpermeability depends on MCs. Indeed, we found that the EP3 receptor is abundantly expressed in BMMCs, as reported previously (38 ). After 5 wk, reconstitution and maturation of the transferred MCs in ear tissues were confirmed by monitoring gene expression of MC-specific genes (Supplemental Fig.…”
Section: Pge 2 -Induced Vascular Hyperpermeability Depends On Ep3 Recsupporting
confidence: 91%
“…To investigate the mechanism of PGE 2 -induced MC activation, we used mouse BMMCs in which EP3 is abundantly expressed (38). We first compared the basic characteristics of WT and Ptger3…”
Section: Pge 2 Triggers Not Only Degranulation But Also Il-6 Productimentioning
confidence: 99%
“…PGE 2 elicits multiple biological responses in mast cells in vitro, for example, adhesion to basement membrane proteins, chemotaxis (17,42), and the production of chemokines (43) and eicosanoids (44), in addition to the up-regulation (37,48) and down-regulation (36, 44) of antigen-mediated mast cell degranulation and cytokine production. The extent and relevance of these responses to PGE 2 in a physiological setting are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC2 Is Required for Optimal PGE 2 -induced PGD 2 and CCL2 Release-In addition to chemotaxis, PGE 2 has also been documented to induce adhesion of mast cells to basement membrane proteins, as well as the production of the chemokine, CCL2, and the eicosanoid, PGD 2 (42)(43)(44). We next determined whether mTORC2 played a role in these responses in addition to chemotaxis.…”
Section: Pge 2 -Induced Activation Of Mtor In Bmmcs Is Mediated By G␣mentioning
confidence: 99%
“…32 PGE 2 has been shown to stimulate chemotaxis and adhesion of MCs through EP. 33,34 In a recent report Morimoto et al 19 demonstrated that EP 3 signaling in MCs generated PGE 2 -induced vasodilatation and subsequent edema formation and speculated that EP 3 -mediated MC activation might be involved in antigen-independent innate immune reactions. Interestingly, we identified that the LTD 4 plus PGE 2 synergism is also EP 3 dependent, strengthening the idea that EP 3 activation might contribute to a proinflammatory role of PGE 2 .…”
Section: Discussionmentioning
confidence: 99%